Neural Differentiation of Wharton\'s Jelly Stem Cells in Three-Dimensional Chitosan Based Culture Environment - E Mansouri (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Wharton Jelly Stem Cells (WJSCs) can be a good option for differentiating and regeneration of nervous system damage. Three dimensional (3D) cell cultures by providing a body-like environment have more advantages than the two dimensional (2D) cell cultures. The aim of this study was to investigate the neural differentiation of these cells in a 3D chitosan based culture environment. METHODS: This experimental study was performed in 4 groups of 2&3D with and without differentiation media on WJSCs. First, to construct the hydrogel, hydroxyl ethyl cellulose was added to chitosan-beta-glycerophosphate solution (8.4: 0.8) (HEC: CH-β-GF). Human WJSCs after isolation by enzymatic method from wartons' jelly of born infant in  Imam Khomeini hospital in Tehran and characterization with flow cytometry, were cultured 5Í10 5 cell in each well of 24-well plate in a 2D and 3D environment using the hydrogel in neural differentiation media for 4 days. Then, the neural differentiation of WJSCs was evaluated by quantitative analysis of β-Tubulin III, Nestin and β-actin (internal control) genes expression by Real Time PCR (RT-PCR). FINDINGS: The results of RT-PCR showed that expression of β-Tubulin III and Nestin genes in WJSCs was significantly increased by the influence of the neural differentiation media in both 2D (more than 4 folds)and 3D (more than 2 folds) culture conditions (p <0.005). But the expression of β-Tubulin III and Nestin in 3D cell culture condition (more than 1.5 folds) was greater than that in the 2D cell culture condition under the influence of the neural differentiation media (p <0.01). CONCLUSION: The results showed that neural differentiation of WJSCs in a chitosan based 3D environment is higher than 2D.